Bibliometric analysis of the S24-7 family and its association with health - Gao, Fangmei; Wang, Fenfen; Wang, Dandan; Du, Guankui; Gao, Fangfang (Frontiers in Microbiology, 2025)
A burgeoning corpus of evidence indicates that S24-7 is integral to human health, with links to obesity, inflammation, metabolism, and dietary interactions. In the present study, we conducted a comprehensive review of the S24-7 literature from the past 10 years, augmented by an evaluation of research trends using both quantitative and qualitative approaches. From the Web of Science (WoS) database, we retrieved 903 research articles and four review articles pertaining to S24-7, also known as Muribaculaceae, that were published between January 1, 2014, and January 1, 2024. Employing software tools such as R, Biblioshiny, VOSviewer, the Bibliometric Analysis Platform, and Pajek, we performed visual mapping and correlation analyses on the collected documents. Our analysis revealed China and the United States as the leading publishers in the field of S24-7 research. The top three academic journals for S24-7 family research are Food and Function, Frontiers in Microbiology, and Nutrition. Among individual contributors, Zhang Y stands out with 31 publications and an h-index of 13, representing 3.42% of the 907 articles analyzed. Jiangnan University leads in institutional output with 46 publications. Keyword analysis underscores that S24-7 research is concentrated on examining the family’s associations with obesity, inflammation, metabolism, and diet. This study highlights notable contributions from various countries, institutions, journals, and researchers, shedding light on the influence of the S24-7 family on human health. It serves to inform future research directions and clinical applications concerning the S24-7 flora.